The parent-of-origin lncRNA MISSEN regulates rice endosperm development - Zhou, Yan-Fei; Zhang, Yu-Chan; Sun, Yu-Meng; Yu, Yang; Lei, Meng-Qi; Yang, Yu-Wei; Lian, Jian-Ping; Feng, Yan-Zhao; Zhang, Zhi; Yang, Lu; He, Rui-Rui; Huang, Jia-Hui; et al. (Nature communications, 2021)
The cereal endosperm is a major factor determining seed size and shape. However, the molecular mechanisms of endosperm development are not fully understood. Long noncoding RNAs (lncRNAs) function in various biological processes. Here we show a lncRNA, MISSEN , that plays an essential role in early endosperm development in rice ( Oryza sativa ). MISSEN is a parent-of-origin lncRNA expressed in endosperm, and negatively regulates endosperm development, leading to a prominent dent and bulge in the seed. Mechanistically, MISSEN functions through hijacking a helicase family protein (HeFP) to regulate tubulin function during endosperm nucleus division and endosperm cellularization, resulting in abnormal cytoskeletal polymerization. Finally, we revealed that the expression of MISSEN is inhibited by histone H3 lysine 27 trimethylation (H3K27me3) modification after pollination. Therefore, MISSEN is the first lncRNA identified as a regulator in endosperm development, highlighting the potential applications in rice breeding. The cereal endosperm is a major determinant of seed size and shape. Here the authors show that a lncRNA, MISSEN , is expressed from the maternally derived allele in rice seeds and regulates a helicase family protein to support efficient nuclear division, distribution and cellularization in the endosperm.